2017
DOI: 10.1002/uog.17388
|View full text |Cite
|
Sign up to set email alerts
|

Cervical length screening for prevention of preterm birth in singleton pregnancy with threatened preterm labor: systematic review and meta‐analysis of randomized controlled trials using individual patient‐level data

Abstract: Objective Cervical length screening by transvaginal sonography (TVS) has been shown to be a good predictive test for spontaneous preterm birth (PTB) in symptomatic singleton pregnancy with threatened preterm labor (PTL). The aim of this review and meta-analysis RR, 0.64 (95% CI,; three trials; 287 participants) and a later gestational age at delivery (MD, 0.64 (95% CI, MD, 4.48 (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 17 publications
0
82
0
11
Order By: Relevance
“…36–39 A 2016 systematic review and meta-analysis of RCTs using individual patient-level data concluded that knowledge of CL in women with symptoms of acute PTL was associated with a significant reduction in PTB o 37 weeks gestation (RR 0.64, 95% CI: 0.44–0.94). 40 However, the other outcomes, which included PTB o36, o34, o32, o30, and o28 weeks gestation, time from randomization to delivery, time from evaluation to discharge, and other neonatal outcomes were not statistically different between those who had knowledge of CL and those who did not. Thus, the clinical impact of CL measurement in this population remains unclear.…”
Section: Introductionmentioning
confidence: 84%
“…36–39 A 2016 systematic review and meta-analysis of RCTs using individual patient-level data concluded that knowledge of CL in women with symptoms of acute PTL was associated with a significant reduction in PTB o 37 weeks gestation (RR 0.64, 95% CI: 0.44–0.94). 40 However, the other outcomes, which included PTB o36, o34, o32, o30, and o28 weeks gestation, time from randomization to delivery, time from evaluation to discharge, and other neonatal outcomes were not statistically different between those who had knowledge of CL and those who did not. Thus, the clinical impact of CL measurement in this population remains unclear.…”
Section: Introductionmentioning
confidence: 84%
“…Nevertheless, the present analysis has some limitations. First, there were no data on cervical length, a maternal condition that is highly associated with the occurrence of sPTB . Second, it was an observational study with retrospective data collection after delivery for variables related to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for sPTB in IVF/ICSI pregnancies is advisable in order to apply preventive strategies [41][42][43][44][45] . Transvaginal cervical length measurement has been used successfully in symptomatic or asymptomatic women to predict sPTB [45][46][47] . It is unlikely that transvaginal cervical length would perform differently in IVF/ICSI pregnancies as compared with spontaneously conceived ones.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%